Ülker Gökberk. Excavating Memory: Bilge Karasu’s Istanbul and Walter Benjamin’s Berlin - Erdoğan, Selen (Zemin, 2021)
Ülker Gökberk. Excavating Memory: Bilge Karasu’s Istanbul and Walter Benjamin’s Berlin. Boston: Academic Studies Press, 2020. xii-275 s., ISBN: 9781644694428.